The utility of animal models to evaluate novel anti-obesity agents - Vickers, Steven P (Blackwell Publishing Ltd, 2011)
The global incidence of obesity continues to rise and is a major driver of morbidity and mortality through cardiovascular and cerebrovascular diseases. Animal models used in the discovery of novel treatments for obesity range from straightforward measures of food intake in lean rodents to long-term studies in animals exhibiting obesity due to the continuous access to diets high in fat. The utility of these animal models can be extended to determine, for example, that weight loss is due to fat loss and/or assess whether beneficial changes in key plasma parameters (e.g. insulin) are evident. In addition, behavioural models such as the behavioural satiety sequence can be used to confirm that a drug treatment has a selective effect on food intake. Typically, animal models have excellent predictive validity whereby drug-induced weight loss in rodents subsequently translates to weight loss in man. However, despite this, at the time of writing orlistat (Europe; USA) remains the only drug currently marketed for the treatment of obesity, with sibutramine having recently been withdrawn from sale globally due to the increased incidence of serious, non-fatal cardiovascular events. While the utility of rodent models in predicting clinical weight loss is detailed, the review also discusses whether animals can be used to predict adverse events such as those seen with recent anti-obesity drugs in the clinic. LINKED ARTICLES: This article is part of a themed issue on Translational Neuropharmacology. To view the other articles in this issue visit http://dx.doi.org/10.1111/bph.2011.164.issue-4